Food pricing and consumer choice: Recommendations for improving affordability for fresh produce in Missouri - Williams, Erica; Participants of the 2024 Fruit; Vegetable Policy Convening; Ellis, Lyndsey; Chatterjee, Sagata; Nguyen, Thi; Anderson, Sarah (Journal of Agriculture, Food Systems, and Community Development, 2025)
Summary This policy and practice brief summarizes input from over 95 participants in the Fruit and Vegetable (Veggie) Policy Convening hosted by A Red Circle and University of Missouri Extension over two and a half days in February 2024. The purpose of the Convening was to discuss policy solutions that could keep fresh produce affordable while ensuring fair compensation for farmers. The goal for the community is to increase access and funding for fruits and vegetables, support community programs, and enhance education efforts that increase fruit and vegetable intake. Breakout room discussions included speakers from academic institutions, community-run nonprofits, and national organizations. Through the Fruit and Veggie Policy Convening, community members and stakeholders provided policy requests to improve food pricing and accessibility options that affect different parts of the food supply chain. Additional policy examples were also informed by searching published journal articles and reports.